Collaboration with the local community to implement sustainable reclamation projects in the mining area - Rahma, AD; Maswahenu, M; Aditama, MH; Mahendra, D; Rahmandhana, AD; Amril, A; Setiawan Putra, LN; Dewi Puspitasari, SI (Mine Closure 2024: 17th International Conference on Mine Closure, 2024)
Sustainability support for communities around the mine areas including social, economic, and environmental aspects is essential. The community is expected to be economically independent and aware of preserving the environment. PT Amman Mineral Nusa Tenggara (AMMAN) has assisted communities around the Batu Hijau mine areas for over 10 years, with one of the most valued and sustainable programs involving community participation in reclamation projects. The community provides Coconets and Ijuk Blankets as materials used for reclamation on the steep slopes. These materials are effective and efficient for covering reclaimed slopes as they resist erosion and are made from unused natural resources. This initiative aims to empower the community to utilise local materials for reclamation, aligning with Sustainable Development Goals (SDGs) 12 (responsible consumption and production) and 15 (life on land). The research analyses the value of social return on investment (SROI) in the community’s Coconet and Ijuk Blanket businesses. The research also uses in-depth interviews with community members, selected through purposive sampling. The results showed that the SROI value has increased from 23.59 to 105.31 within five years, indicating a significant impact of the program on the community. Community business actors also supply market demand from other areas, showcasing the program's scalability. Empowering the community through this reclamation program has been a best practice example for community-driven economic development as it builds sustainable capacity and improves livelihoods. Through involvement in this program, community members gain economic benefits and contribute to sustainable environmental management.
Keywords: community empowerment; livelihoods; reclamation; sustainability; SROI